2020
DOI: 10.1073/pnas.2015830117
|View full text |Cite
|
Sign up to set email alerts
|

Genome analyses reveal the hybrid origin of the staple crop white Guinea yam ( Dioscorea rotundata )

Abstract: White Guinea yam (Dioscorea rotundata) is an important staple tuber crop in West Africa. However, its origin remains unclear. In this study, we resequenced 336 accessions of white Guinea yam and compared them with the sequences of wild Dioscorea species using an improved reference genome sequence of D. rotundata. In contrast to a previous study suggesting that D. rotundata originated from a subgroup of Dioscorea praehensilis, our results suggest a hybrid origin of white Guinea yam from crosses between the wild… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 33 publications
1
51
0
2
Order By: Relevance
“…8a ). The few intra-chromosome differences observed could represent bona fide rearrangements between species or, possibly, imperfections in the D. rotundata v2 assembly 21 that could have arisen from the reliance on linkage mapping to order and orient D. rotundata scaffolds, especially in recombination-poor pericentromeric regions of the genome. Under the assumption that D. rotundata chromosomes are in 1:1 correspondence with D. alata chromosomes, we can provisionally assign four large but unmapped D. rotundata scaffolds to chromosomes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8a ). The few intra-chromosome differences observed could represent bona fide rearrangements between species or, possibly, imperfections in the D. rotundata v2 assembly 21 that could have arisen from the reliance on linkage mapping to order and orient D. rotundata scaffolds, especially in recombination-poor pericentromeric regions of the genome. Under the assumption that D. rotundata chromosomes are in 1:1 correspondence with D. alata chromosomes, we can provisionally assign four large but unmapped D. rotundata scaffolds to chromosomes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here we describe a chromosome-scale reference genome for D. alata and a dense 10k marker consensus genetic linkage map from five populations involving seven distinct parental genotypes. Comparison of the D. alata reference genome with the recently sequenced genomes of the distantly related D. rotundata 21 and D. zingiberensis 22 reveals substantial conservation of chromosome structure between D. alata and D. rotundata but considerable rearrangement relative to more deeply divergent D. zingiberensis lineage. Analysis of the D. alata genome supports the existence of ancient polyploidy events shared across Dioscoreales, and reveals chromosome rearrangements after the most recent pan-Dioscoreales genome duplication.…”
Section: Introductionmentioning
confidence: 97%
“…Plants of a yam clone in a farmer's field are genetically homogenous with negligible recombination rates, as farmers select their planting material from tubers and not from botanical seed. However, the molecular evidence on ennobled cultivars showed that the tubers collected by farmers from wild environments are often a mixture of wild (D. abyssinica and D. praehensilis) and interspecific hybrid (D. rotundata × wild species) yams (Scarcelli et al, 2006(Scarcelli et al, , 2017Sugihara et al, 2020). This could partly explain the origin of the genetic admixture identified among the Beninese white Guinea yam accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Most species in the genus Dioscorea (Dioscoreaceae) are dioecious [ 125 ] and have XY sex chromosomes [ 81 , 126 , 127 ], suggesting dioecy may have evolved ~80 million years ago (MYA) [ 128 ]. In D. alata a recent genetic map uncovered a ~10 Mb male-specific region of the Y (MSY) [ 81 ].…”
Section: Advances In Sex-determination Gene Identificationmentioning
confidence: 99%